Measuring the Impact of Technology, Politics, and Human Resources on Inclusive Economic Growth in Indonesia - Cyntia Dwi Lestari; Farida Rahmawati (Fakultas Ekonomi dan Bisnis Islam UIN Alauddin Makassar, 2021)
Economic growth is no longer just to improve the economy alone, but economic growth must also pay attention to the welfare of the community and be carried out by paying attention to the quality of the economic growth. Good economic growth is not only temporary but long term. One of the government's efforts by this concept is to create inclusive and sustainable economic growth. The measure of the quality of economic growth can be seen through the Inclusive Economic Development Index (IGI). However, achieving inclusive economic growth is not easy. The novelty of the research is that inclusive economic growth is not only approached with an economic approach but non-economic variables are also included, to see further this interrelation. The method used in this research is quantitative with a descriptive approach. Panel regression analysis models and techniques using stata. The results of this study indicate that technology and human resources have a significant and positive effect on inclusive economic growth in Indonesia from 2017 to 2019. Meanwhile, politics has a positive but not significant effect on inclusive economic growth in Indonesia from 2017 to 2019. From the results of this study, it can be seen that also that technology, politics, and human resources simultaneously have a significant and positive effect on inclusive economic growth in Indonesia from 2017 to 2019. The implications of this research include, among others, the government needs to optimize HR productivity. Keywords: Inclusive Economy; Political; Human Resources; Technology